The Social Dimension of Multi-Racial Advertising: Its Impact on Consumers’ Attitude - (:unkn) unknown (My University, 2009)
Since the end of the apartheid regime, the number of advertisements casting actors from different racial backgrounds simultaneously has significantly increased. Comments about this development are multi-faceted. While some observers praise this technique as the ideal social mirror of the “new” South Africa, others criticize it as a pervasive commercial tactic. Consistent with this debate, it is important for brands to understand consumers’ perceptions of multi-racial advertising. Indeed, these perceptions are also assumed to influence consumers’ attitude towards the advertised brand. Based on the attribution theory, this study investigates whether South African companies, by integrating a multi-racial feature in an advertisement, create the perception amongst consumers that their advertisement is socially responsible and, in so doing, increase their brand equity. The empirical results of this study support that consumers’ attitude towards a brand is significantly influenced by the extent to which they attribute a social responsibility to its advertisements. Nevertheless, it is also found that using multi-racial advertising is a necessary but not sufficient condition to generate this social attribution.
Keywords: African Research